Discourse on the Application of Cardiac Surgery Techniques in Indonesia and Consent for Medical Actions in Health Law - Riyantika, Annisa (NEGREI: Academic Journal of Law and Governance, 2024)
Informed Consent is an important thing in medical services, recently there have been cases of problems that start from the incompatibility of Informed Consent with factual actions carried out by the hospital. This has been explained in Jo Law No. 44 of 2009 concerning hospitals Article 37 paragraph 1 which states that every medical action taken in the hospital must obtain the consent of the patient and his family. The purpose of this article is to analyze the Informed Consent Relationship between Doctors and Patients Legally in the Application of Cardiac Surgery Techniques in Indonesia and to analyze the Application of Informed Consent in the Application of Cardiac Surgery Techniques. The method used in this research is the normative juridical method. The normative juridical approach is carried out by conducting a study of the principles, regulations and legislation in force with regard to the legal issues to be discussed. The results of this study are the existence of an informed consent relationship between doctors and patients and the application of informed consent in cardiac surgery in Indonesia.